EFFECTS OF GREEN TEA EXTRACT ON GRAAFIAN FOLLICLES AND SERUM17b-ESTRADIOL IN MONOSODIUM GLUTAMATE-EXPOSED RATS - Syami Yulianti et al (Baqai Journal of Health Sciences)
Monosodium glutamate (MSG) is widely consumed as food preservative and flavor enhancer. MSG administration in rats has been reported to induce oxidative stress causing damage to ovarian histological structures by affecting number of follicles and production of reproductive hormones. Polyphenols in green tea are suggested as powerful antioxidants that inhibit free radicals responsible for causing oxidative stress. This study aimed to investigate the effects of various doses of green tea on the Graafian follicles and serum 17b-estradiol levels in rats exposed to MSG. The design of this study was the post test only control group experiment. A total of twenty-five white female rats (Rattus norvegicus) were divided into 5 treatment groups. MSG in a dose of 0.7 mg/g body weight (BW) and green tea extract (Camellia sinensis) in doses of 0.7, 1.4, and 2.8 mg/day were administered orally over 30 day period starting after the rats proestrus phase. Graafian follicles were counted using light microscope while serum 17b-estradiol level was measured using ELISA kit and the data was statistically analyzed using one-way ANOVA. A significant difference of Graafian follicles number (p<0.04) and serum 17b-estradiol level (p<0.006) was observed across the treatment groups. The results showed that green tea extract at a dose of 1.4 mg/day significantly increased the number of Graafian follicles and serum 17b-estradiol level in female white rats exposed to MSG.